Should you fix again? An unusual fracture of a distal epiphyseal radius fracture – A Case Report. - Sabit Numan Kuyubasi; Bunyamin Ari; Sermet Inal; Alaaddin Oktar Uzumcugil; Suleyman Kaan Oner (Journal of the Pakistan Medical Association, 2021)
Introduction: Currently Salter-Harris (SH) classification is generally used in physeal fractures. It is reliable and valed in many cases. In general concept, although this clasification system describes many different fracture configurations, there is an unclassifed group. Case: Here we present an eleven years old boy who underwent surgery after an unclassifed fracture of distal radial epiphysis according to SH. The main reason for the research was that we could not decide about the treatment initially after the first operation. We discussed the current classsifications near SH and essentials on the neccesity of surgical approach. Conclusion: Surgical attempt must be done in such cases which can not be decided whether if a SH type 2 or 3. Beside this situation, an attempt must be done for the classification of the fracture (Ogden tip 2b, Sferoupulos tip 3). Continuous...